A Review on Why Researchers Apply External Magnetic Field on Nanofluids - M'hamed, Beriache; Nor Azwadi, Che Sidik; Mohammad Noor Afiq Witri, Muhammad Yazid; R., Mamat; G., Najafi; G. H. R., Kefayati (Elsevier, 2016)
This paper reviewed the application of external magnetic field on nanofluids. So far, nanoparticles have been used in various areas such as manufacturing, electrical and electronics, automotive and recently biomedical applications. On the other hand, nanofluids with suspension of magnetic nanoparticles have attracted noteworthy attention due to its numerous applications in industries and engineering. In line with fast development of this type of nanofluid, the purpose of this paper is to further understand the effect of external magnetic field on nanofluids properties and fluid flow, which is a key issue that influenced both the nanofluid properties and control of fluid flow for application. The conclusions and important summaries were also presented according to the data collected.